2020
DOI: 10.3390/ma13225202
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Fine to Coarse Aggregate Ratio for the Workability and Mechanical Properties of High Strength Steel Fiber Reinforced Concretes

Abstract: High-strength concrete is used to provide quality control for concrete structures, yet it has the drawback of brittleness. The inclusion of fibers improves the ductility of concrete but negatively affects the fresh properties of fiber-reinforced concrete. The effects of different fine to coarse aggregate ratios on the fresh and hardened properties of steel fiber reinforced concrete were investigated in this study. Mixtures were prepared with various fine to coarse aggregate (FA/CA) ratios incorporating 1% stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Past research has investigated the effect of CAMZs of 8, 13, and 20 mm and fiber dosages of 0.0%, 1.0%, and 2.0% on the flexural performance of steel FRC [11][12][13][14]. According to Olivito and Zuccarell [15], to ensure a uniform and efficient fiber distribution, the steel fiber length should be two times more than the CAMZ.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has investigated the effect of CAMZs of 8, 13, and 20 mm and fiber dosages of 0.0%, 1.0%, and 2.0% on the flexural performance of steel FRC [11][12][13][14]. According to Olivito and Zuccarell [15], to ensure a uniform and efficient fiber distribution, the steel fiber length should be two times more than the CAMZ.…”
Section: Introductionmentioning
confidence: 99%
“…Cepuritis et al [27] reported an improvement in concrete workability when the fines content increases. In the same way, Iqbal Khan et al [28] showed that the concrete workability was better when fine aggregate to coarse aggregate ratio reaches 0.8. Other works [29] noted 22% increase in workability for concrete with QWS sand instead of NS.…”
Section: Superplasticizer Dosagementioning
confidence: 73%
“…Previous studies [28,29,34,35] have already revealed a decrease in the workability of mortar with fiber inclusion. The workability is affected by the length, surface morphology, and surface area of fibers [36].…”
Section: Workability Of Mortar Incorporating Fibersmentioning
confidence: 94%
“…Workability of mortar, measured using a flow table for each size (the proportion for each fiber length included is 0.3% by volume). Previous studies [28,29,34,35] have already revealed a decrease in the workability of mortar with fiber inclusion. The workability is affected by the length, surface morphology, and surface area of fibers [36].…”
Section: Workability Of Mortar Incorporating Fibersmentioning
confidence: 94%